Financial Condition's Role in Tax Evasion: A TPB Perspective - Mangoting, Yenni; Saputra, Ferren Fidelia (Jurnal ASET (Akuntansi Riset), 2024)
The purpose of this study is to examine the influence of TPB dimensions on taxpayers' intention to commit fraud by testing the effect of financial condition intervention on taxpayers as a factor that can change taxpayers' intention to commit fraud. This research employs a survey approach, where data is collected through questionnaires. Data collection methods were distributed manually and online to individual taxpayers aged 17 and above, totaling 200 out of 213 respondents' data that could be collected. Data analysis technique used is SEM-PLS (Partial Least Square). The results of this study indicate that all TPB dimensions, namely attitude, subjective norm, and perceived behavior control, are able to influence the intention to commit tax evasion. Moderation testing shows that the interaction of financial condition with each component of TPB can change taxpayers' intention to commit tax evasion. The implications of the research results indicate that regulators need to map taxpayers' financial conditions. This is useful to change taxpayers' paradigm that tax payment is part of citizenship obligations rather than economic sacrifice. This study offers a new direction in expanding the tax evasion research model by involving TPB dimensions and incorporating situational factors such as financial condition as additional determinants or intervention factors.